Is exposure and response prevention treatment for obsessive–compulsive disorder as aversive as we think? - Lee, Yong; Rees, Clare (Wiley-Blackwell Publishing Ltd., 2011)
Background: Meta-analytical studies have confirmed that exposure and response prevention (ERP) is the psychological treatment of choice for obsessive–compulsive disorder (OCD). Anecdotal evidence suggests that patients drop out of ERP because of the aversive nature of the treatment. Methods: In this study, eight individuals diagnosed with OCD described their experience of ERP treatment in one-to-one semi-structured interviews. Qualitative data analysis was used to identify common themes across participants. Results: Common themes were categorised into a) Experience of ERP, b) specific treatment factors, c) non-specific treatment factors, and d) quality of life impact. Conclusions: Several specific and non-specific variables emerged as significantly impacting on the experience of completing ERP. A number of important themes emerged that provide special areas for consideration for minimising distress to clients when treating OCD using ERP.